P17 Respiratory impact of diabetes mellitus in people without a primary diagnosis of chronic lung disease. (12th November 2015) - Ruickbie, S; Prasad, A; Jones, PW; Baker, EH
Abstract : Introduction: In the UK, around 3 million people currently have a diagnosis of diabetes mellitus and the prevalence is increasing rapidly. Microvascular and macrovascular complications of diabetes are widely recognised, but the respiratory impact is less well understood. In people with chronic lung disease, diabetes mellitus is associated with worse lung function, impaired health status and more frequent exacerbations (Kinney et al . Diabetes Care. 2014;37:389–95). The aim of our study was to determine the respiratory impact of diabetes in people without a primary diagnosis of chronic lung disease. Methods: Unselected patients attending for elective coronary angiography March–July 2015 were invited to take part in a prospective observational study (primary aim to investigate the association between coronary atheroma and airflow obstruction). Participants underwent clinical assessment and spirometry prior to the procedure. Results: 250 of 294 (85%) people approached took part. Seventy five (30%) had diabetes mellitus. People with diabetes were of similar age and gender to those without diabetes, but had greater body mass index, central adiposity, blood glucose and HbA1c (Table 1 ). Despite no differences in history of smoking or respiratory illness (Table 1), people with diabetes had significantly lower forced vital capacity (FVC) and higher forced expiratory volume (FEV1 ): FVC ratio than those without diabetes. After adjustment for age, gender, body mass index, waist: hip ratio and smoking history, diabetes was an independent predictor of FEV1 : FVC (partial eta 2 0.03, p = 0.007), but not FVC. People with diabetes had more respiratory symptoms (Table 1). They were more likely to give a history of recurrent chest infections (diabetes 14(19%); no diabetes 11(6%), p = 0.004) and reported more chest infections (diabetes 0.6 ± 1.6; no diabetes 0.2 ± 0.9, p = 0.007) in the past year. After adjustment for age, waist: hip ratio, body mass index, smoking, FEV1 : FVC and co-existing respiratory disease, diabetes was an independent predictor of recurrent chest infections (odds ratio 2.81 (95% confidence intervals 1.04–7.73), p = 0.045). Conclusions: Diabetes mellitus is associated with worse lung function, increased respiratory symptoms and more frequent chest infections, independent of smoking and prior respiratory illness. The burden of diabetes-associated respiratory disease on patients and the NHS is likely to increase as diabetes becomes more prevalent.